(untitled) (A Social Science and Entrepreneurship Journal, 2024)
This study explores the preservation of cultural heritage among selected Mёranao residents in Tubod, Lanao del Norte, with a focus on their roles as custodians of indigenous knowledge in the face of globalization. These residents serve as teachers, counselors, ceremony leaders, and dispute settlers, preserving and passing on vital cultural traditions and artisanal skills that are essential for community identity and sustainability. Employing a descriptive qualitative approach, data were gathered through purposive sampling of 100 Mёranao respondents using a modified survey questionnaire. The results highlight the interconnected roles of these residents in maintaining cultural continuity, while also addressing the challenges brought about by modernization and migration. The study underscores the importance of preserving cultural heritage to enhance community visibility, empowerment, and contribute to poverty alleviation. It advocates for the integration of traditional knowledge into modern initiatives to ensure the survival of cultural identity for future generations.